How Men's Movement Participants View Each Other. - Fox, John (Journal of Men's Studies)
This study compares the opinions of men's movements' participants of each other. Nineteen profeminist, 17 men's rights, and 18 mythopoetic activists returned surveys. Overall, the respondents had little awareness of each other. The profeminist and men's rights respondents had negative views of each other, while the profeminists were more familiar with the mythopoetic men's issues than with men's rights issues. Further, profeminist respondents were split regarding their opinions of the mythopoetic men's movement. Men's rights respondents had lukewarm opinions of the mythopoetic men's movement, and the mythopoetic men's movement participants were not familiar enough with either the profeminist of men's rights men's movements to respond. This study shows that men's movement rhetoric is unreliable in its representation of how men's movement participants view each other. Reprinted by permission of the publisher.